Application of Employment Agreements as a Legal Remedy to Protect The Rights and Obligations of Contract Workers - Siregar, Dahris (JUSTISI, 2025)
The study aims provide an explanation and comparison of the legal aspects of Law Number 13 of 2003, which regulates the rights and responsibilities of workers who have contract status. This research method uses normative juridical law, so the focus of the research is processing legal documents and collecting and analyzing current legal elements based on secondary data sources. Novelty the legalization of the Manpower Law Number 13 of 2023, the status of contract worker or PKWT has sparked debates and demonstrations. This research provides an overview of each issue addressed at the base, unit, or company level in a bipartite cooperation organization. The problem will be resolved in the industrial relations court to provide the right result for the parties. The existence of a business contract is made in written form, making it a valid and legally binding written agreement for the parties. The study results emphasizing the need for a balance between workers' duties and rights, the mechanism for resolving industrial relations disorders as stipulated in Law Number 2 of 2004 through negotiations, conciliation, arbitration, and Industrial Relations Courts, as well as legal certainty and protection of human rights in employment contracts. Conclusion workers are required to comply with the company's regulations, be willing to change positions, maintain and maintain the confidentiality of the position, and comply with the Company's working hours regulations. If there is a dispute between workers and employers, the settlement must follow the provisions of the collective bargaining agreement. The problem is resolved through a bipartite cooperation institution, both at the base, unit, and company levels, and if the solution has been taken but does not give satisfactory results, then the problem will be resolved through the Industrial Relations Court.